ANALISIS MATRIK IE PADA PERANAN WANITA SEBAGAI PELAKU UMKM DALAM PENINGKATAN PEREKONOMIAN DI WILAYAH KECAMATAN NGANTANG KABUPATEN MALANG SEBAGAI DASAR DALAM PEMBANGUNAN - Warter Agustim; Moch. Nurhidayat (Unitri Press, 2020)
This study aims to determine the appropriate steps in describing, analyzing, and interpreting the factors related to the empowerment of women's business associations that are able to raise the economic standard of the family and become an independent and economically prosperous family. Strategy determination is applied through three steps, the input stage, matching and decision. The input stage is carried out through the use of the Internal Factor Evaluation Matrix (IFE) and the External Factor Evaluation Matrix EFE). In the IFE matrix there is a total score of 242 and in the EFE matrix a score of 356 is obtained. From the analysis of internal and external factors, it is followed by the matching stage using the IE Matrix method. The IE matrix uses the scores obtained in the IFE matrix and the EFE matrix showing that the role of women as MSME actors in economic improvement is in cell II, with a strategy that can be used, namely developing and building so that they are in a strong position.